Tricyanidoferrates(−IV) and Ruthenates(−IV) with Non‐Innocent Cyanido Ligands. Issue 29 (15th June 2021) - Jach, Franziska; Wagner, Frank R.; Amber, Zeeshan H.; Rüsing, Michael; Hunger, Jens; Prots, Yurii; Kaiser, Martin; Bobnar, Matej; Jesche, Anton; Eng, Lukas M.; Ruck, Michael; Höhn, Peter
Abstract: Exceptionally electron‐rich, nearly trigonal‐planar tricyanidometalate anions [Fe(CN)3 ] 7− and [Ru(CN)3 ] 7− were stabilized in LiSr3 [Fe(CN)3 ] and AE3.5 [M(CN)3 ] (AE=Sr, Ba; M=Fe, Ru). They are the first examples of group 8 elements with the oxidation state of −IV. Microcrystalline powders were obtained by a solid‐state route, single crystals from alkali metal flux. While LiSr3 [Fe(CN)3 ] crystallizes in P63 /m, the polar space group P63 with three‐fold cell volume for AE3.5 [M(CN)3 ] is confirmed by second harmonic generation. X‐ray diffraction, IR and Raman spectroscopy reveal longer C−N distances (124–128 pm) and much lower stretching frequencies (1484–1634 cm −1 ) than in classical cyanidometalates. Weak C−N bonds in combination with strong M−C π‐bonding is a scheme also known for carbonylmetalates. Instead of the formal notation [Fe −IV (CN − )3 ] 7−, quantum chemical calculations reveal non‐innocent intermediate‐valent CN 1.67− ligands and a closed‐shell d 10 configuration for Fe, that is, Fe 2− . Abstract : The electron‐rich cyanidometalates [Fe(CN)3 ] 7− and [Ru(CN)3 ] 7− represent the first examples of group 8 elements with an oxidation state of −IV. DFT calculations reveal a nominal d 10 s 0 configuration, which corresponds to an effective charge of 2−. The high negative charge also weakens the C−N bonds by the population of antibonding states.